Alice E Suas Experiências De Aprendizagem: Ensinando E Aprendendo Matemática Com Uma Estudante Com Deficiência Intelectual - Silva, Edeson Dos Anjos (2024)
This study titled "Alice and Her Learning Experiences: Teaching and Learning Mathematics with a Student with an Intellectual Disability," presents data collected in a research in the Doctoral Program in Education of the Graduate Program of the Federal University of Espírito Santo – UFES. The main objective of this study was to understand the processes of producing mathematical knowledge in the teaching and learning relationship with a student with intellectual disability, during her final years of elementary school in the context of the ordinary classroom. Specifically, the aim was to: analyze the didactic-pedagogical organization related to the teaching of mathematics in the field of focus of study; understand the role of pedagogical mediation in the process of acquiring mathematical concepts; understand how the student with intellectual disabilities internalizes the scientific concepts of mathematics from inclusive pedagogical practices in the school environment, based on cultural-historical contributions. In preparing this study, the methodological framework adopted, based on its qualitative nature, assumed the panorama of the case study from a historicalcultural perspective, essentially dialoguing with Vygotsky, Bakhtin and their collaborators, as well as renowned theorists in the field of special education who understand the human being as a being who, regardless of physical, mental or sensory characteristics, produces knowledge and culture at the same time as appropriating the culture and knowledge of the other subjects in their social group. In summary, it can be emphasized that these specific objectives allowed the full achievement of the general objective of this study, since it made it possible to analyze the processes of production of mathematical knowledge in the relationship between teaching and learning with a student with intellectual disabilities in her final years of elementary school in the context of the ordinary classroom. To this end, the study revealed that the school should perform its social function, as well as the education professionals who mediate the teaching, learning and development process of Alice. In order for Alice, the subject with intellectual disabilities, to be conceived as a historical and cultural subject, who was constituted through the environment, of the other, with the other, she is a subject who produces and reproduces history and culture. To this end, inclusive pedagogical practices must be developed in such a way that mathematical teaching and learning becomes a source of intellectual and social development for individuals with intellectual disabilities. With this, we confirm the thesis that Alice and other students with intellectual disabilities can appropriate mathematical knowledge, when these subjects are offered material, techniques, instruments and procedures that enable the reach of knowledge, abstractions and transformations of spontaneous and scientific knowledge historically produced by humanity.